2011
DOI: 10.1136/bcr.01.2011.3752
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplantation among identical twins: therapeutic dilemmas

Abstract: A case of the successful kidney transplantation among two homozygous twins is presented here. Prior to the familial kidney transplantation from the identical twins, the patient underwent peritoneal and haemodialyses as well as cadaveric kidney transplant from an unrelated donor. In this patient, vascular accessibility was poor and the second familial transplantation was performed urgently. Transplanted kidney function proved excellent; however, the issues of the best immunosuppressant to be selected are under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
0
4
0
5
Order By: Relevance
“…In the setting acute rejection, the preservation of renal function that is more important for graft survival. [11,13] This study also provides urine output measurement as early clinical parameters, that collected on a routine basis to monitor graft function immediately after transplantation to provide an insight into the long-term function of the graft. Other studies have indicated that the magnitude of urine output is one of the most clinically used predictors for graft function immediately after reperfusion.14 We evaluated the urine output from the POD 0 till patient discharged (Fig5).…”
Section: Discussionmentioning
confidence: 99%
“…In the setting acute rejection, the preservation of renal function that is more important for graft survival. [11,13] This study also provides urine output measurement as early clinical parameters, that collected on a routine basis to monitor graft function immediately after transplantation to provide an insight into the long-term function of the graft. Other studies have indicated that the magnitude of urine output is one of the most clinically used predictors for graft function immediately after reperfusion.14 We evaluated the urine output from the POD 0 till patient discharged (Fig5).…”
Section: Discussionmentioning
confidence: 99%
“…In identical-twin transplant recipients, the requirement and degree of immunosuppressive agents remains uncertain. 12 - 14 Increasing evidence has shown that monozygous twins can and do differ genetically in response to the environment and aging, with changes mainly affecting single base pairs, and rarely at large genomic regions. 6 , 15 Whether such minor differences are capable of triggering allograft rejection between identical twins remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…este se llevaron a cabo nuevos trasplantes en pacientes vivos no relacionados, sin embargo, debido a la barrera inmunológica, la tasa de fracaso fue alta, y se inició el uso de azatioprina y prednisolona [2][3][4][5][6][7][8][9][10][11] .…”
unclassified
“…En los años siguientes, el entendimiento de los mecanismos de la reacción inmunológica condujo a un notable aumento de la inmunoterapia farmacológica 6,9 . En la actualidad, pese a su desarrollo, persiste aún el temor de rechazo agudo y pérdida del injerto; en este ámbito, es bien conocido que el trasplante renal con HLA idéntico tiene una incidencia menor de rechazo agudo y una mejor supervivencia del injerto, comparado con aquel entre receptores no idénticos [12][13][14][15] .…”
unclassified
See 1 more Smart Citation